2015
DOI: 10.1259/bjr.20150224
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lung cancer by enhanced dual-energy CT: association between three-dimensional iodine concentration and tumour differentiation

Abstract: Iodine volume measured by DECT could be a valuable functional imaging method to estimate differentiation of primary lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 28 publications
5
31
1
Order By: Relevance
“…The recent technical advance of dual‐energy CT (DECT) has provided the material‐specific imaging, also known as material decomposition, which can separate several numbers of substances, such as water, iodine, calcium, uric acid, and fat . Especially, quantitative information for iodine distribution, among the DECT‐based material decomposition techniques, has been considered a promising tool for lesion characterization to distinguish not only malignancy from benignity but also hyperdense cystic lesions or hematomas from enhancing lesions . In the head and neck region, several studies showed iodine concentration (IC) could be useful in CT imaging of cervical lymph nodes or patients with underlying neck malignancy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent technical advance of dual‐energy CT (DECT) has provided the material‐specific imaging, also known as material decomposition, which can separate several numbers of substances, such as water, iodine, calcium, uric acid, and fat . Especially, quantitative information for iodine distribution, among the DECT‐based material decomposition techniques, has been considered a promising tool for lesion characterization to distinguish not only malignancy from benignity but also hyperdense cystic lesions or hematomas from enhancing lesions . In the head and neck region, several studies showed iodine concentration (IC) could be useful in CT imaging of cervical lymph nodes or patients with underlying neck malignancy .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Especially, quantitative information for iodine distribution, among the DECT-based material decomposition techniques, has been considered a promising tool for lesion characterization to distinguish not only malignancy from benignity but also hyperdense cystic lesions or hematomas from enhancing lesions. 7,8,[10][11][12][13][14][15][16][17][18] In the head and neck region, several studies showed iodine concentration (IC) could be useful in CT imaging of cervical lymph nodes or patients with underlying neck malignancy. [19][20][21][22] Until now, a few studies have evaluated IC of thyroid nodules using the DECT data sets to find the malignancy or intranodular hemorrhage; however, they decided the individual CT images for quantification without the detailed topographic knowledge based on ultrasound, which is widely considered as reference imaging modality to assess thyroid nodule.…”
Section: Introductionmentioning
confidence: 99%
“…These research findings indicate that iodine uptake at the arterial phase on contrast CT may be associated with some sort of tumor histopathology such as angiogenesis and hypoxic cell. Our recent study demonstrated that the three-dimensional iodine-related attenuation (3D-IRA; also known as “iodine volume”) of primary lung cancers measured by contrast-enhanced DE-CT was significantly associated with their differentiation grade [ 15 ]. Tumor grade correlates directly with microscopic tumor invasiveness [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Iwano et al . [ 27 ] reported that the iodine volume during the delayed phase of dual-phase dynamic DE-CT correlated negatively with SUV max in 27 patients with primary lung cancer.…”
Section: Discussionmentioning
confidence: 99%